Clinical and neuroimaging features of acute ischemic stroke presented with vertigo - Xiao-lan YANG; Fei SHEN; Jia-lüe HUA; Jie-xing QIN; Jie-ru ZHOU; Yan-sheng LI (Chinese Journal of Contemporary Neurology and Neurosurgery, 2019)
Objective To summarize the clinical and neuroimaging features of acute ischemic stroke presented with vertigo and explore its pathogenesis. Methods The clinical data of 81 patients with acute ischemic stroke in posterior circulation initiated as vertigo from January 2014 to October 2017 were retrospectively analyzed, including clinical symptoms and signs, laboratory indexes, neuroimaging and TOAST classification. Results Eighty-one patients were divided into isolated vertigo group (N = 18) and non-isolated vertigo group (N = 63). Compared with non-isolated vertigo group, patients of isolated vertigo group had higher rates of coronary heart disease [8/18 vs. 15.87% (10/63); adjusted χ2 = 5.062, P = 0.024] and atrial fibrillation [7/18 vs. 14.29% (9/63); adjusted χ2 = 3.907, P = 0.048]. Patients in isolated vertigo group also had higher rate of nystagmus [10/18 vs. 30.16% (19/63); χ2 = 3.929, P = 0.047] than that in non-isolated vertigo group. Imaging examination showed the lesion of 16/18 patients of isolated vertigo group was located in cerebellum, and the ratio was significantly higher than that of non-isolated vertigo group (Z = -2.289, P = 0.022). TOAST classification showed the type of 8/18 patients of isolated vertigo group was large artery artherosclerosis (LAA), and 6/18 patients was cardioembolism (CE). Conclusions Patients with isolated vertigo caused by acute ischemic stroke had higher rate of coronary heart disease and atrial fibrillation than those with non-isolated vertigo. The infarcts were mostly located in the cerebellum and mainly caused by large artery artherosclerosis or cardioembolism.